2001
DOI: 10.1590/s1519-566x2001000200009
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of entomopathogenic fungi with neonicotinoid insecticides

Abstract: Compatibilidade de Fungos Entomopatogênicos com Inseticidas NicotinóidesRESUMO -O efeito fungitóxico, in vitro, de três inseticidas neonicotinóides, acetamiprid (Saurus 200 PS), imidacloprid (Confidor 700 GrDA) e thiamethoxam (Actara 250 WG) em três concentrações (RM = recomendação média para campo, 0,7 RM e 1,3 RM), foi avaliado sobre os fungos entomopatogênicos Beauveria bassiana, Metarhizium anisopliae e Paecilomyces sp. O efeito dos inseticidas sobre a germinação dos conídios, o crescimento vegetativo e a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
24

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 3 publications
(5 reference statements)
3
63
0
24
Order By: Relevance
“…The compatibility of M. anisopliae with thiamethoxam and lambdacyhalothrin is in agreement with other studies (Batista Filho et al, 2001;Cavalcanti et al, 2002;Loureiro et al, 2002;Neves et al, 2001;Rampelotti-Ferreira et al, 2010). Despite the insecticide thiamethoxam+ lambdacyhalothrin is a combination of two compatible insec- ticides, it was scored as moderately toxic in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The compatibility of M. anisopliae with thiamethoxam and lambdacyhalothrin is in agreement with other studies (Batista Filho et al, 2001;Cavalcanti et al, 2002;Loureiro et al, 2002;Neves et al, 2001;Rampelotti-Ferreira et al, 2010). Despite the insecticide thiamethoxam+ lambdacyhalothrin is a combination of two compatible insec- ticides, it was scored as moderately toxic in this study.…”
Section: Discussionsupporting
confidence: 92%
“…However, no toxicity of imidacloprid to M. anisopliae was observed by Loureiro et al (2002), and Neves et al (2001) showed that the product did not inhibit germination, radial growth or fungal reproduction. Nevertheless, according to the last authors, deltametrin presented marked toxicity to M. anisopliae and other entomopathogenic fungi.…”
Section: Commercial Namementioning
confidence: 96%
“…Several studies have analyzed the effects of pesticides on entomopathogenic fungi in order to determine their compatibility for pest control (Poprawski & Majchrowicz 1995, Neves et al 2001, Loureiro et al 2002. Most of these reports were conducted by adding products to the synthetic culture media used for fungal growth.…”
mentioning
confidence: 99%
“…The mechanism of action of neonicotinoid insecticides as inducers of disease resistance in plants is still unclear. Shown promising results in controlling citrus canker (FRANCIS et al, 2009), but did not affect germination, vegetative growth and pathogenicity of fungi (NEVES et al, 2001).…”
Section: A Mancha Marrom De Altenária Ou Mma (Alternaria Alternata)mentioning
confidence: 99%